The Meaning of Ma’rifatullāh and How It Affects Islamic Education - Awaliyah Fitri, Sofia Ratna; Mahmud, Mahmud (TAJDID, 2022)
Ma'rifat is a Sufi discipline that emphasizes the importance of knowing the Creator through Islamic teachings, specifically the Qur'an and Hadith or the Prophet's sunnah, which are internalized in the Prophet's life. ma’rifatullāh face increasingly complex life challenges in the modern era. This causes humans to lose sight of their sacred obligation to perform their duties and functions as abid on earth. Using the literature review method, this study attempts to elaborate on the concept of ma'rifat and its relevance to Islamic education. ma’rifatullāh is a concept used to develop students' noble character, and it turns out that the concept of ma'rifat is more than just knowledge; it is an increase in self-awareness that leads to obedience and piety to Allah.